Influence of menu labeling on food choices of University of the Philippines Diliman Students - Ballesteros, Maria Krizhia R.; Morales, Janica Marie T.; Peren, John Paul B. (College of Home Economics, University of the Philippines Diliman, 2022)
An increasing prevalence of overweight and obese among adult individuals in the Philippines was reported in 2018. Frequent consumption of food outside the home has contributed to this increase. In the United States of America and Canada, among the strategies to address the growing problem of overweight and obesity is menu labeling. Menu labeling is the inclusion of nutrient content in menus to encourage informed food-related decisions among consumers. In the Philippines, the implementation of menu labeling remains voluntary among food establishments. In this study, the influence of menu labeling on the food choices of UP Diliman students was explored. The study was conducted using the descriptive qualitative design which allowed for in depth understanding of the participants’ beliefs and attitudes. Twenty five participants were selected using purposive sampling to participated in a focus group discussion (FGD) via an online conferencing platform. Transcribed data were thematically analyzed. Six themes were observed: (i) inclusion of menu labeling is beneficial but needs considerations;(ii) healthy food choices are important but not priority; (iii) interest in using menu labels; (iv) personal food choices triumphs nutritional quality; (v) social interaction when dining affects food choices; and (vi) limited availability of menu labeling. UP Diliman students have a positive attitude towards menu labeling and perceive it as beneficial. However, participants expressed concerns regarding its psychological and economic impact on consumers. Specifically, its tendency to trigger eating disorders and anxiety and the added cost of labeling menus to consumers. Also, participants anticipated limited use of menu labels due to individual factors like food cravings, mood, cost, and social factors like the individuals they dine with. Moreover, providing nutrition education and using graphical representations for the labels were suggested by the participants to increase interest of consumers to use menu labels. Nevertheless, menu labeling is useful in guiding students to make healthier food choices, thereby contributing to improved diet.